2014
DOI: 10.1186/1471-2407-14-955
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts induce high mobility group box 1 and contribute to resistance to doxorubicin in breast cancer cells

Abstract: BackgroundCancer-associated fibroblasts and high mobility group box 1 (HMGB1) protein have been suggested to mediate cancer progression and chemotherapy resistance. The role of such fibroblasts in HMGB1 production in breast cancer is unclear. This study aimed to investigate the effects of cancer-associated fibroblasts on HMGB1 expression in breast cancer cells and its role in chemotherapeutic response.MethodsBreast cancer-associated fibroblasts (BCFs) and non-tumor-associated fibroblasts (NTFs) were isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 55 publications
0
83
0
Order By: Relevance
“…It was reported that IL-17A was overexpressed by colorectal CAFs in response to chemotherapy, with expression validated directly in patient-derived specimens without culture, suggesting that chemotherapy promotes tumor microenvironment remodeling to support the tumor cellular hierarchy through secreted factors (5). Amornsupak et al (17) reported that pre-treatment of breast cancer cells with breast cancer-associated fibroblasts induced a degree of resistance to doxorubicin in accordance with the increased level of secreted high mobility group box 1 (HMGB1), highlighting the potential of stromal fibroblasts to contribute to chemoresistance in breast cancer cells partially through fibroblast-induced HMGB1 production (17).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that IL-17A was overexpressed by colorectal CAFs in response to chemotherapy, with expression validated directly in patient-derived specimens without culture, suggesting that chemotherapy promotes tumor microenvironment remodeling to support the tumor cellular hierarchy through secreted factors (5). Amornsupak et al (17) reported that pre-treatment of breast cancer cells with breast cancer-associated fibroblasts induced a degree of resistance to doxorubicin in accordance with the increased level of secreted high mobility group box 1 (HMGB1), highlighting the potential of stromal fibroblasts to contribute to chemoresistance in breast cancer cells partially through fibroblast-induced HMGB1 production (17).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro assays have also demonstrated that CAFs induce resistance to chemotherapy via secreting cytokines (16,22,23). Besides chemotherapy agents, inhibiting CAFs may also enhance the effects of bevacizumab (rhuMab VEGF, Avastin) even in bevacizumab-resistant GC cells (24), which is similar to the selective susceptibility of Ī±-SMA-deficient vessels to bevacizumab (25).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, the stromal response in the MTD and LDM groups treated with 5-Fu or capecitabine was examined. CAFs were investigated on the basis of their proposed roles in supporting drug-resistance (16). As the characteristics of CAFs are rather distinctive in different tumor types and stages, without homogeneity, in order to compare the CAF evolution in GC following different patterns of chemotherapies, matched samples from identical xenografts of the control, MTD, and LDM groups were stained for the CAF marker Ī±-SMA to reflect the difference (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of-tumor-associated macrophages (TAM), one of the most important types of inflammatory leukocytes (9), exhibit a crucial role in the chemotherapy-resistance of patients with lung cancer (10). Furthermore, cancer-associated fibroblasts have been demonstrated to contribute to the doxorubicin-resistance of breast cancer cells (11). Gene polymorphisms in DNA repair pathways and multi-drug resistance gene 1 (MDR1) could also contribute to the response of non-small cell lung cancer (NSCLC) to chemotherapy (12).…”
Section: Introductionmentioning
confidence: 99%